1995
DOI: 10.2307/3579158
|View full text |Cite
|
Sign up to set email alerts
|

Thiazolidine Prodrugs of Cysteamine and Cysteine as Radioprotective Agents

Abstract: The need for protection against the toxic effects of ionizing radiation comes from many different directions: occupational exposure, nuclear accidents, environmental sources and protection of normal tissue during the therapeutic irradiation of cancer. Sulfhydryl-containing compounds, including cysteamine and L-cysteine, have long been known to possess radioprotective properties, but their therapeutic utility is limited by their side effects at radioprotective doses. To avoid this drawback, thiazolidine prodrug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 34 publications
2
21
0
Order By: Relevance
“…Therefore, for both chronic and acute irradiation conditions, there appears to be a window for optimum radioprotection with minimal undesired chemotoxic effects on the V79 cells. Similar observations were made by Roberts et al (35) for the radioprotector MEA. (36).…”
Section: Dmf As a Function Of Dmso Concentrationsupporting
confidence: 88%
“…Therefore, for both chronic and acute irradiation conditions, there appears to be a window for optimum radioprotection with minimal undesired chemotoxic effects on the V79 cells. Similar observations were made by Roberts et al (35) for the radioprotector MEA. (36).…”
Section: Dmf As a Function Of Dmso Concentrationsupporting
confidence: 88%
“…Thiol-containing compounds, including cysteamine and cysteine are known to possess radioprotective properties, but their therapeutic utility is limited by their side effects at therapeutic doses. To avoid this, prodrugs with 'shielded' thiol groups, such as thiazolidine compounds and alpha-methyl-homocysteine thiolactone, have been examined showing positive beneficial effects (Roberts et al 1995;Koch et al 1997). There is a very interesting analogy of Met with these prodrugs, since Met also comprises 'shielded' -SH group, which becomes free following the decomposition, in the form of homocysteine (Bern et al 2010) or CH 3 SH (as shown here).…”
Section: Resultsmentioning
confidence: 99%
“…First, the creation of hydroxyl radicals is limited by dehydration of the cell cytoplasm, while their diffusion is limited by molecular crowding (Mazur 1984). Second, the cell interior is filled with free radical scavengers such as cysteine (Roberts et al 1995). Third, the slower diffusion of free radicals in frozen or supercooled water is expected to reduce the frequency of strand breaks in frozen cells (Huttermann et al 1992; Ohshima et al 1996).…”
Section: Exposure Of Cells To X-ray Beammentioning
confidence: 99%